From your shadow to the orbit of the Moon. Issue 2 (1st April 2019) - Lee, Charles; Reilly, Thomas
Abstract : Charles Lee and Thomas Reilly argue in favour of simple old-fashioned talks – with a few calculations thrown in – as a useful tool for outreach. Abstract: Charles Lee and Thomas Reilly argue in favour of simple old-fashioned talks – with a few calculations thrown in – as a useful tool for outreach.